Urban coyotes - Carson, Mary Kay (Scientists in the field (Clarion Books), 2024)
"The fourth largest metropolitan area in North America is home to more than nine million people and a surprisingly large population of coyotes. Join the wildlife scientists of the Urban Coyote Research Project as they carry on their twenty-five-year mission: Studying the coyotes of Cook County, Illinois, home to the city of Chicago. Explore questions such as 'Where did the coyotes come from-and why?,' 'Are they a danger to Chicagoans?,' and 'Do predators create healthier urban ecosystems?' with real-life scientists in the field. Started by urban ecologist Stan Gehrt in the late 1990s when coyotes were first noticed entering the Chicago region, the Urban Coyote Research Project's mission is to help coyotes and human city dwellers live together in peace"--Publisher.